A political and economic dictionary of South Asia - Schöttli, Jivanta (Taylor and Francis, 2015)
Thanks to its emerging markets, nuclearization and the internet revolution, South Asia is increasingly at the forefront of current affairs. This invaluable reference source seeks to make the region accessible to business travellers as well as to the general reader. The range of subjects to be covered includes major political processes and events of South Asia (elections and electoral politics, political slang, political parties, diplomacy and territorial divisions), domestic and foreign policy, key personalities, political and economic institutions, sub-national groupings and units (regions, c